In-service education of elementary school teachers in the Philippines and its implications for Nepal - Pradhan, Ratna Man 1936- (s.n.], 1966)
The author gathered information about the in-service education of elementary school teachers in the Philippines, from which probable implications for Nepal were derived. This information includes the national aims and objectives of the in-service education in the Philippines, how in-service training programs of elementary school teachers are organized, administered, supervised and evaluated at different levels, how it is financed, the problems encountered and the implications of the findings that may have relevance to the educational system in Nepal.